Investigating the influence of taurine on thiol antioxidant status in Wistar rats with a multi-analytical approach - Sochor, J; Nejdl, Lukáš; Ruttkay-Nedecký, Branislav; Bezděková, Andrea; Lukešová, Kateřina; Zítka, Ondřej; Cernei, Natalia; Mareš, Petr; Pohanka, Miroslav; Adam, Vojtěch; Babula, Petr; Beklová, Miroslava; et al. (Journal of Applied Biomedicine, 2014)
Taurine (2-aminoethanesulfonic acid) is an organic acid widely distributed in animal tissues. It is involved in many physiological processes. Thus, it is widely discussed especially due to its antioxidant properties. In this study, we focused on the effect of taurine supplementation on the concentration of antioxidants in blood plasma and erythrocytes of Wistar rats. Taurine was applied in feed mixture in the dosage of 0, 1, 250, 500, 750, 1000, 1500, 2000, 2500, 3000, 3500 and 4000 mg/kg. We monitored both enzymatic and non-enzymatic antioxidants – glutathione peroxidase, glutathione reductase, and superoxide dismutase and reduced/oxidized glutathione and metallothionein. Using three different methods 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS), Ferric Reducing Antioxidant Power (FRAP) and free radicals, we determined antioxidant capacity. In addition, we monitored levels of uric acid and glucose. Our results revealed significant changes in both enzymatic and non-enzymatic parameters with the increasing taurine supplementation.
Keywords: Glutathione; superoxiddismutasa; Superoxide Dismutase; Glucose; metalothionein; Peroxiredoxins; erytrocyty; glutathionreduktasa; zvířata; Rats; peroxiredoxiny; oxidační stres; Taurine; Metallothionein; Dose-Response Relationship, Drug; mužské pohlaví; glukosa; Plasma; Statistics as Topic; Oxidative Stress; kyselina močová; glutathionperoxidasa; Rats, Wistar; krysa rodu Rattus; thiol antioxidant; glutathiondisulfid; potkani Wistar; statistika jako téma; krevní plazma; Uric Acid; Animals; glutathion; vztah mezi dávkou a účinkem léčiva; Glutathione Peroxidase; Erythrocytes; Glutathione Disulfide; Glutathione Reductase; taurin; Male